PENGARUH NILAI TUKAR RUPIAH DAN JUMLAH UANG YANG BEREDAR TERHADAP ROA PADA BANK CENTRAL ASIA SYARIAH PERIODE 2013-2022 - Lina Nofiana; Fitri Nur Anisa (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of the Rupiah Exchange Rate and Total Money in Circulation on Return on Assets (ROA) at Bank Central Asia Syariah for the period 2013-2022. The method in this research is Quantitative Descriptive. The data analysis methods used include: Descriptive Analysis, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test, and Autocorrelation Test), Determination Coefficient Test (R^2), Regression Analysis (Simple Linear Regression Test and Multiple Linear Regression Test), Hypothesis Test (t test (partial), F test (simultaneous)). The results of this study indicate that the Rupiah Exchange Rate (X1) partially has no effect on Return On Asset (Y) at Bank Central Asia Syariah for the Period 2013-2022 the results show that tcount < ttable (0.949 < 2.36462) with a significance value of 0.374> 0.05, it can be said that Ho1 is accepted and Ha1 is rejected. Total Money in Circulation (X2) partially has no effect on Return on Assets (Y) because the results show that tcount < ttable (1.001 < 2.36462) with a significance value of 0.350 > 0.05). The hypothesis results show that Ho2 is accepted and Ha2 is rejected. Simutaneously the Rupiah Exchange Rate and the Amount of Money in Circulation affect the Return on Assets at Bank Central Asia Syariah for the 2013-2022 Period. This is because Fcount> Ftable (6.910> 4.74) and reinforced by a significance value of 0.022 <0.05, so based on the results obtained, it means that Ho3 is rejected and Ha3 is accepted. The Coefficient of Determination of 0.664 indicates that the Rupiah Exchange Rate (X1) and Total Money in Circulation (X2) on Return On Asset (Y) have an influence of 66% and the remaining 34% is influenced by other factors.